2021
DOI: 10.1136/jnnp-2021-327206
|View full text |Cite
|
Sign up to set email alerts
|

Early predictors of disability of paediatric-onset AQP4-IgG-seropositive neuromyelitis optica spectrum disorders

Abstract: ObjectiveTo describe onset clinical features predicting time to first relapse and time to long-term visual, motor and cognitive disabilities in paediatric-onset aquaporin-4 antibody (AQP4-IgG) neuromyelitis optica spectrum disorders (NMOSDs).MethodsIn this retrospective UK multicentre cohort study, we recorded clinical data of paediatric-onset AQP4-IgG NMOSD. Univariate and exploratory multivariable Cox proportional hazard models were used to identify long-term predictors of permanent visual disability, Expand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The female predominance in NMOSD occurring in children and adolescents is seen at the ratio of 1.5:1 and 3.25:1 respectively ( 55 ). The other study has shown a 5:1 F:M ratio of AQP4-antibody seropositive patients younger than 12 years ( 56 ). This being said, elderly individuals are also at risk of developing NMOSD.…”
Section: The Effect Of Sex On the Age Of Clinical Onset And Diseases ...mentioning
confidence: 88%
“…The female predominance in NMOSD occurring in children and adolescents is seen at the ratio of 1.5:1 and 3.25:1 respectively ( 55 ). The other study has shown a 5:1 F:M ratio of AQP4-antibody seropositive patients younger than 12 years ( 56 ). This being said, elderly individuals are also at risk of developing NMOSD.…”
Section: The Effect Of Sex On the Age Of Clinical Onset And Diseases ...mentioning
confidence: 88%
“…Cognitive and psychiatric presentations of NMOSD may lead to permanent disability due to delayed recognition and misdiagnosis. Common localization for cognitive and psychiatric relapses in AQP4+ NMOSD have included lesions in the cerebral hemispheres (4), diencephalon (5), and corpus callosum (7), and both of our cases demonstrated prominent involvement of the latter. There have been reported cases of autoimmune encephalitis, in particular NMDA receptor antibody positive encephalitis, co-existing with AQP4+ NMOSD (8,9).…”
Section: Discussionmentioning
confidence: 56%
“…Similarly to MS, the degree of recovery from AQP4+NMOSD attacks is influenced by age and attack severity, with better recovery observed in younger individuals with lower deficits at nadir ( 26 , 78 80 ). In a retrospective study on 182 subjects with AQP4+NMOSD, the length of the longest spinal cord lesion measured on MRI was found to be a predictor of more severe residual disability ( 81 ), while another study showed that CSF levels of glial fibrillary acidic protein during acute attacks correlated with the length of spinal cord lesions and with the EDSS at 6 months from the index attack ( 82 ).…”
Section: Discussionmentioning
confidence: 99%